Food insecurity in the households of children with autism spectrum disorders and intellectual disabilities in the United States: Analysis of the National Survey of Children's Health Data 2016–2018. (November 2021) - Karpur, Arun; Vasudevan, Vijay; Lello, Angela; Frazier, Thomas W; Shih, Andy
Individuals with autism spectrum disorder and co-occurring intellectual disabilities experience substantial challenges in accessing needed supports. This research aimed to understand the prevalence and factors associated with food insecurity among families of children with autism spectrum disorder and co-occurring intellectual disabilities. Utilizing the National Survey of Children's Health (2016–2018) data, this article illustrated that the households of children with autism spectrum disorder and co-occurring intellectual disabilities were about two times more likely to be food insecure than the households of children without disabilities. Furthermore, the households of children with autism spectrum disorder were 1.5 times more likely, and those with other disabilities were 1.3 times more likely to be food insecure than the households of children without disabilities. Implications of these findings in the context of the COVID-19 pandemic are discussed. Lay abstract: Families of children with autism spectrum disorder are more likely to experience financial strain and resulting food insecurity due to additional cost of care, disparate access to needed services, and loss of income resulting from parental job loss. Utilizing nationally representative data, this analysis indicates that the families of children with autism spectrum disorder and co-occurring intellectual disabilities are twice as likely to experience food insecurity than families of children without disabilities after adjusting for various factors. Several factors, ranging from state-level policies such as Medicaid expansion to individual-level factors such as higher utilization of emergency room services, were associated with the higher prevalence of food insecurity in families of children with autism spectrum disorder and co-occurring intellectual disabilities. Implications of these findings on programs and policies supporting families in the COVID-19 pandemic are discussed.